Diversity of native woody regeneration in exotic tree plantations and natural forest in Southern Philippines. Issue 1 (2nd January 2017) - Tulod, Adrian M.; Casas, Jupiter V.; Marin, Rico A.; Ejoc, Jocyl Ann B.
ABSTRACT: The use of exotic species in reforestations is one of the highly criticized forest policies in the Philippines, mainly due to their perceived negative impacts on biodiversity conservation. To ascertain the influence of exotic plantations on native flora establishments, we inventoried the structure, composition, and diversity of understory woody regeneration in three exotic stands in Southern Philippines and compared them to adjacent second growth forest. The mean total density of regeneration did not differ significantly among the stands, except for the separate density of saplings and seedlings where natural forest had significantly the lowest and highest density, respectively, over the exotic stands. Teak ( Tectona grandis L.) and mangium ( Acacia mangium Willd.) stands generally had the bigger basal area, indicating the dominance of saplings in these areas. A low diversity characterized the four stands with the lowest and highest diversity indices observed, respectively, in the mahogany ( Swietenia macrophylla King) and natural forest. Despite their proximity, each stand exhibited uniqueness in species composition, with some of the endangered species observed only in the exotic stands. Therefore, it would be interesting to know how continued protection of these stands would affect the trajectory of succession of native species over time.